Решение уравнения 6*(2х+3)-4*(2х-4)=0​

veronicavasilyk veronicavasilyk    3   08.04.2021 08:53    0

Ответы
marusi220 marusi220  08.04.2021 09:00

Відповідь:

x = -8,5

Покрокове пояснення:

6*(2х+3)-4*(2х-4)=0​

12x + 18 - 8x + 16 = 0

12x - 8x = -18 - 16

4x = -34

x = -34 : 4

x = -8,5

ПОКАЗАТЬ ОТВЕТЫ
voVIK2008 voVIK2008  08.04.2021 09:00

Відповідь:

-8,5

Покрокове пояснення:

6*(2х+3)-4*(2х-4)=0

12х+18-8х+16=0

12х-8х=-18-16

4х=-34

х=-34/4

х=-8,5

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика